Microbiota awareness levels of medical students: the case of Trakya university - İsmail Davarci; Pınar Zehra Davarci (BMC Medical Education)
Abstract Background Human microbiota is noteworthy for its ability to encode a much greater variety and quantity of proteins than human cells. Despite its dynamic and complex nature, it has been associated with healthy living for over a century. The knowledge and attitudes of healthcare professionals, especially physicians, influence the use of pro-prebiotic interventions to modulate the microbiota. This study aimed to examine the awareness of medical students about the microbiota and the factors influencing their awareness. Methods The study was conducted between May 15 and August 15, 2023, with the participation of 235 medical students. The students were administered a 13-item questionnaire and the Microbiota Awareness Scale (MAS). The questionnaire and scale were administered face-to-face, and the results were statistically analyzed. Results The students’ MAS total mean score was 70.34 ± 8.15. The MAS scores of medical students in the 4th, 5th, and 6th grades who underwent clinical training, those who conducted research on microbiota independently, those who had previously used prebiotics/probiotics, and those who rated themselves highly on microbiota knowledge were statistically higher. Conclusions The study revealed that students’ awareness of the microbiota increased with advancing years of medical education, reaching a high level by the time of graduation. To enable future physicians to effectively communicate this knowledge to the public and incorporate it into clinical practice, it is crucial to provide comprehensive education on microbiota, probiotics, and prebiotics during medical training. Additionally, promoting scientific research and organizing activities in these areas are essential for fostering deeper understanding and practical application.